A rare complication with a single dose of alendronate. (21st September 2010) - Munigoti, Srinivasa; Frazer, Ricky; Rees, Alan; Blackshaw, Guy; Thomas, Gareth; Roberts, Aled
Abstract : The authors present a case of an 84-year-old patient who presented to the emergency department with sudden onset abdominal pain radiating to the neck. The patient's medication included warfarin, and alendronate, which was started by the general practitioner 2 days prior to presentation. Initial systemic examination and investigations, including chest x-ray, were unremarkable. Within 24 h of presentation the patient developed bilateral pneumonia with effusions. Due to continued clinical deterioration over the next 48 h, a CT thorax was performed that showed evidence of large oesophageal perforation with mediastinitis and gas in the mediastinum. The patient was treated with an expandable metal stent, bilateral chest drains, broad spectrum antibiotics, antifungals and total parenteral nutrition. Over a period of 8 weeks the patient made an excellent recovery. This rare case illustrates the importance of vigilance for the life-threatening complication of oesophageal perforation with alendronate treatment.